Teaching Writing Using Electronic Portfolio in the Multimedia Lab at Widya Mandala Surabaya Catholic University - Wuri Soedjatmiko; Johanes Leonardi Taloko (TEFLIN Journal: A publication on the teaching and learning of English, 2003)
This paper attempts to share the teaching of descriptive writing using electronic portfolio (e-portfolio) in the multimedia lab where students can write according to their own pace. Given indivi-dual electronic folders, they can continue writing whenever they want. The students can revise their first draft following comments given by the tutor or peers, or continue to the next assignment put in the tutors folder. Microsoft Word also provides tools, "track changes " and "insert and view comments", which enable students to freely and responsibly accept or reject suggestions given by the tutor. As a result, corrections, comments and revisions have caused improvements in describing things in more detailed ways, and less on the grammar and vocabulary mastery. However, only 25% of the students think their progress relates to an ability to better describe things; the rest believe their improvements are more in grammar and vocabulary mastery. E-portfolio provides a lot of practice, which enables the students to directly read comments and corrections given by the tutor and peers. Another significant finding is that the tutor must use various delivery techniques to cope with students different learning preferences.